Peningkatan Kompetensi Fisioterapis dalam Pemeriksaan Flat Foot Menggunakan Foot Posture Index (FPI-6) di RS Muhammadiyah Palembang - Yudiansyah Yudiansyah (IKesT Muhammadiyah Palembang, 2026)
Flat foot (pes planus) is a foot postural deformity characterized by the reduction or collapse of the medial longitudinal arch, which may lead to biomechanical disturbances, pain in the lower extremities, and decreased ability to perform daily activities. Accurate and standardized assessment is essential in physiotherapy practice to support proper diagnosis and appropriate intervention planning. However, preliminary observations at the Physiotherapy Unit of Muhammadiyah Hospital Palembang revealed that flat foot assessments had not yet been conducted optimally, with variations in the examination methods used. This activity aimed to enhance the competence of physiotherapists in performing systematic and evidence-based flat foot assessments using the Foot Posture Index (FPI-6). The program was conducted in February 2026 at Muhammadiyah Hospital Palembang and involved physiotherapists as participants. The activity employed several methods, including educational sessions, scientific discussions, demonstrations, and hands-on practice in performing flat foot examinations using the Foot Posture Index (FPI-6) and the Navicular Drop Test. Evaluation was carried out through pre-test and post-test assessments to measure participants’ improvement in knowledge. The evaluation results demonstrated an increase in participants’ knowledge from an average score of 62% in the pre-test to 87% in the post-test, representing a 25% improvement following the training. In addition, participants showed improved skills in assessing foot structure, determining Foot Posture Index scores, and interpreting examination results in a more systematic manner. The activity also produced educational materials in the form of a flat foot examination poster that can serve as a practical clinical guide within the hospital setting. In conclusion, this training activity proved effective in improving physiotherapists’ competence in conducting standardized flat foot examinations. The enhancement of these competencies is expected to support improved quality of physiotherapy assessment and contribute positively to the quality of physiotherapy services for outpatient care